The temporal trend of cause-specific mortality: comparing Estonia and Lithuania, 2001 - 2019 - Alexander Tran; Relika Stoppel; Huan Jiang; Kawon Victoria Kim; Shannon Lange; Janina Petkevičienė; Ričardas Radišauskas; Mindaugas Štelemėkas; Tadas Telksnys; Anush Zafar; Jürgen Rehm (BMC, 2022)
Abstract Background Despite being two Baltic countries with similar histories, Estonia and Lithuania have diverged in life expectancy trends in recent years. We investigated this divergence by comparing cause-specific mortality trends. Methods We obtained yearly mortality data for individuals 20 + years of age from 2001-2019 (19 years worth of data) through Statistics Lithuania, the Lithuanian Institute for Hygiene, and the National Institute for Health Development (Estonia). Using ICD-10 codes, we analyzed all-cause mortality rates and created eight major disease categories: ischemic heart disease, cerebrovascular disease, all other cardiovascular disease, cancers (neoplasms), digestive diseases, self-harm and interpersonal violence, unintentional injuries and related conditions, and other mortality (deaths per 100,000 population). We used joinpoint regression analysis, and analyzed the proportional contribution of each category to all-cause mortality. Results There was a steeper decline in all-cause mortality in Estonia (average annual percent change, AAPC = -2.55%, 95% CI: [-2.91%, -2.20%], P < .001) as compared to Lithuania (AAPC = -1.26%, 95% CI: [-2.18%, -0.57%], P = .001). For ischemic heart disease mortality Estonia exhibited a relatively larger decline over the 19-year period (AAPC = -6.61%, 95% CI: [-7.02%, -6.21%], P < .001) as compared to Lithuania (AAPC = -2.23%, 95% CI: [-3.40%, -1.04%], P < .001). Conclusion Estonia and Lithuania showed distinct mortality trends and distributions of major disease categories. Our findings highlight the role of ischemic heart disease mortality. Differences in public health care, management and prevention of ischemic heart disease, alcohol control policies may explain these differences.